Sustainable Marketing of Healthcare in Indonesia with Religiosity and Health Promotion Clean Healthy Lifestyle - Erlina Puspitaloka Mahadewi; Ahmad Hidayat Sutawidjaya; Daru Asih; Ngadino Surip; Arman Harahap (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Health promotion has received a boost that includes actions at the individual and community levels, strengthening health systems and multi-sectoral partnerships that can be directed at specific health conditions in pandemic. It should also include a settings-based approach to promoting health in specific settings such as schools, hospitals, workplaces, residential areas and communities. Health promotion needs to be built into all policies and if used efficiently will result in health marketing outcomes for healthcare providers and positive behavior change in clean healthy lifestyle. The results of this study indicate that the patient's perception of a clean and healthy life based on the benefit dimension is 89.50%, based on the trust dimension 83.35%, the patient's perception is based on the risk dimension 81.55%, the patient's perception is based on the 85.22% religiosity dimension, and patient satisfaction, in generally common perception is 84.90%. Global acceptance that health promotion and clean and healthy lifestyle (CHLB) behavior in social marketing science is determined by many factors outside the health system. Healthcare issues can be effectively addressed with a holistic approach by empowering individuals and communities to take action for their health.